Pengaruh Psychological Capital terhadap Stres Kerja pada Perawat di Rumah Sakit Naili DBS Kota Padang - Aditya Briliant Ananta; Suci Rahma Nio (ARZUSIN, 2026)
Although nurses play an important role in providing professional healthcare services, work situations characterized by high pressure, heavy workloads, demands of responsibility, and emotional strain in nursing care have the potential to cause job stress. In this context, psychological capital is regarded as a positive psychological resource that can help nurses cope with work pressure. This study aimed to determine the effect of psychological capital on nurses’ job stress at Naili DBS Hospital, Padang City. This study employed a quantitative approach with a simple linear regression design. The study population included all nurses at Naili DBS Hospital, Padang City, with a sample of 97 nurses selected through the total sampling technique. Data were collected using Likert scales based on the aspects of psychological capital and job stress, and were then analyzed statistically. The results showed that psychological capital had a significant effect on nurses’ job stress, with a correlation coefficient (R) of 0.620, a coefficient of determination (R²) of 0.385, and an F value of 59.41 with a significance of p < 0.001, indicating that the research hypothesis was accepted. These findings indicate that psychological capital plays a role in influencing nurses’ level of job stress, although there are still other factors, such as social support, work–life balance, and leadership style, that also have the potential to affect job stress. Thus, this study emphasizes the importance of strengthening psychological capital as part of a human resource management strategy in hospitals, while also providing a theoretical contribution to the study of occupational psychology and practical implications for the development of a more supportive work environment for nurses.